Advancements and Challenges in Additive Manufacturing: Future Directions and Implications for Sustainable Engineering - Raffi Mohammed; Abdul Saddique Shaik; Subhani Mohammed; Kiran Kumar Bunga; Chiranjeevi Aggala; Bairysetti Prasad Babu; Irfan Anjum Badruddin (Advance Sustainable Science Engineering and Technology, 2025)
This study explores the recent advancements in additive manufacturing (AM) and its significant effects on various industries such as aerospace, automotive, medical, and casting. The research investigates how AM has the potential to enhance design flexibility, reduce weight, and optimize material performance through developments like adaptive algorithms, topology-based process planning, and multi-objective optimization techniques. These advancements have resulted in near-net-shape casting, improved surface finishes, and enhanced structural integrity. However, the widespread adoption of AM in the commercial sector faces challenges such as high costs, limited material compatibility, and inconsistent build quality. This paper assesses these limitations and suggests solutions such as enhanced design algorithms, AI-driven process monitoring, and the creation of sustainable materials to address them. By overcoming these barriers, AM can smoothly integrate into industrial environments and revolutionize manufacturing processes. The study emphasizes the importance of further exploration of AM's potential to drive innovation, sustainability, and productivity across different sectors.